2013
DOI: 10.1021/np400674t
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intestinal Permeability of Vicenin-2 and Lychnopholic Acid from Lychnophora salicifolia (Brazilian Arnicão) Using Caco-2 Cells

Abstract: Lychnophora salicifolia, commonly known as "arnicão", is used as an anti-inflammatory agent and as a flavoring agent in the Brazilian traditional spirit "cachaça". In this work, the permeation process of vicenin-2 (1) and lychnopholic acid (2) (major secondary metabolites from the hydroalcoholic extract) was investigated using Caco-2 cells. For this investigation, a new HPLC-DAD method was developed and validated for the quantification step. It was observed that 2 crosses the Caco-2 cell monolayer by passive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…VIC and LA were isolated from L. salicifolia leaves as described before. 14 The internal standard (IS) coumarin was purchased from Sigma (USA).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…VIC and LA were isolated from L. salicifolia leaves as described before. 14 The internal standard (IS) coumarin was purchased from Sigma (USA).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…It is well know that Lychnophorinae produce metabolites of therapeutic importance, such as terpenoids (mono‐, sesqui‐, di‐ and triterpenes and sesquiterpene lactones) and phenolic compounds (flavonoids and cinnamic acid derivatives) (Vichnewski & Gilbert, ; Vichnewski et al ., ; Herz et al ., ; Dias Barros et al ., ; Oliveira et al ., ; Grael et al ., ; Dos Santos et al ., ; Kanashiro et al ., ; Taleb‐Contini et al ., ; Silvério et al ., ; Keles et al ., ; Dos Santos et al ., ; Baldin et al ., ; De Souza et al ., ; Abreu et al ., ; Silvério et al ., ; Gouvea et al ., ; Saúde‐Guimarães, Raslan & Oliveira, ). In addition, many studies have investigated the chemotaxonomy of Lychnophorinae because of the chemical richness that characterizes the subtribe (Bohlmann et al ., , b; Herz et al ., ; Bohlmann et al ., ; Zdero et al ., ; Bohlmann et al ., ; Bohlmann & Jakupovic, ; Borella et al ., ; Lunardello et al ., ; Borella et al ., ; Vichnewski et al ., ; Sacilotto, Sartori & Vichnewski, ; Sartori et al ., ; Sakamoto et al ., , ; Keles et al ., ; Sakamoto et al ., ; Souza et al ., ; Lusa et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that type 2 diabetes is due to several reasons including defect in impaired GLUT 4 vesicle translocation from the cytosolic phase to cell membrane. It has been shown that the VN transport is mediated by GLUT 4 vesicle, (i.e), VN utilizes GLUT 4 system for its intracellular transport . In addition, a recent report has shown that VN inhibits various enzymes linked with diabetes including PTP1B in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the VN transport is mediated by GLUT 4 vesicle, (i.e), VN utilizes GLUT 4 system for its intracellular transport. 12,13 In addition, a recent report has shown that VN inhibits various enzymes linked with diabetes including PTP1B in vitro. However, the study observed a low PTP1B inhibitory activity than the standard, urosolic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation